Chronic Stress and Unhealthy Dietary Behaviors among Low-Income African-American Female Caregivers - Lim, Sungwoo (Curr Dev Nutr, 2020)
BACKGROUND: Chronic stress increases the risk of excess intake of calorie-dense foods. Low-income minority caregivers in the United States are cumulatively exposed to stressors and unhealthy foods, but evidence of this association is limited in this population group. The objective of the current study was to assess the association between chronic stress and unhealthy dietary behaviors among low-income African-American caregivers in Detroit, Michigan. METHODS: Data came from Detroit Dental Health Project, a longitudinal study of pairs of African-American caregivers and children during 2002–2007. A sample of 912 female caregivers were included and their baseline (2002–2003) survey responses were analyzed to identify those with chronic stress and patterns of dietary behaviors. The likelihood of having unhealthy dietary behaviors was compared between chronically stressed caregivers and others, and the mediator role of depressive symptoms or current smoking was tested. RESULTS: Approximately 10% of caregivers experienced chronic stress as they all reported discrimination, residential movement, and lack of social support. Twenty-five percent of the caregivers were found to have an unhealthy dietary pattern characterized by excess intake of high fatty foods and soda. Chronically stressed caregivers were more likely to exhibit unhealthy dietary behaviors (prevalence ratio: 1.39; 95% CI: 1.05, 1.84), and this relation was significantly mediated by depressive symptoms, not current smoking. CONCLUSIONS: These findings suggest that chronic stress played a role in negatively influencing dietary behaviors. As this association might be mediated by depressive symptoms, an intervention to reduce depressive symptoms can be considered as an effective strategy to promote healthy dietary behaviors among chronically stressed minority caregivers.